(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Diabetes mellitus has emerged as one of India’s most critical public health challenges of the 21st century. With over 101 million people already living with diabetes and another 136 million in the prediabetic state as of 2023–2024, India bears the largest absolute burden of diabetes globally.